Tu-Teng-Cao Extract Alleviates Monosodium Urate-Induced Acute Gouty Arthritis in Rats by Inhibiting Uric Acid and Inflammation. (22nd April 2020) - Yao, Rongmei; Geng, Zihan; Mao, Xin; Bao, Yanyan; Guo, Shanshan; Bao, Lei; Sun, Jing; Gao, Yingjie; Xu, Yingli; Guo, Bo; Meng, Fengxian; Cui, Xiaolan
Abstract : Gouty arthritis is an inflammatory joint disease closely related to hyperuricemia. It is characterized by deposition of monosodium urate crystals in the joints, resulting in an intense inflammatory process and pain. Control of hyperuricemia and anti-inflammation treatments are the main therapeutic approaches. However, the commonly used drugs for inhibiting uric acid and acute gouty arthritis have obvious gastrointestinal and renal toxicity; thus, there is an urgency to develop new alternative therapeutic drugs. An extract of Tu-Teng-Cao (TTC), a compound drug used in traditional Chinese medicine, has been widely applied to the clinical treatment of arthritis. In this study, we investigated the therapeutic effects of TTC on gouty arthritis. In this study, an animal model of acute gouty arthritis with hyperuricemia was established using potassium oxonate and monosodium urate crystals. After treatment with TTC, the results showed obvious therapeutic effects on the rat model of acute gouty arthritis. The treatment significantly attenuated the degree of ankle swelling, inflammation, and dysfunction index, and the levels of proinflammatory cytokines. In addition, TTC has significant antihyperuricemia activity in rats with hyperuricemia induced by potassium oxonate. Histological evaluation showed that TTC relieved pathological damage in rats with acute gouty arthritis induced by monosodium urate crystals. All the groups treated with TTC showed improvement in cartilage degeneration, cell degeneration, synovial hyperplasia, and inflammatory cell invasion in the ankle joint of rats. TTC significantly alleviated swelling, inflammation, and bleeding of the renal corpuscle and convoluted tubules of rats. The results of this study suggest that TTC is capable of treating gouty arthritis and decreasing ankle injury through the control of uric acid and inflammation.